2014
DOI: 10.1007/s00246-014-0966-7
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Complete Atrioventricular Septal Defect in Infants with Down Syndrome: Outcomes and Long-Term Results

Abstract: In clinical practice, the combination of congenital heart disease (CHD) with malformations of other organs occurs in about 10 % of cases, including chromosomal disease with heart defects, which are observed mainly with certain syndromes. In the Bakoulev SCCS (Moscow, Russian Federation), from 01.2005 to 01.2011, complete atrioventricular septal defect (CAVSD) repair was performed on 163 patients (5.6 ± 3.0 months) with Down Syndrome (DS) using the single-patch (n = 40) and the two-patch (n = 123) methods. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 15 publications
3
33
1
4
Order By: Relevance
“…Early surgical studies reported worse surgical outcomes in patients with Down syndrome undergoing repair for complete atrioventricular septal defect compared with patients without genetic syndromes . More recently, several studies have demonstrated equal or decreased risk of in‐hospital mortality for patients with Down syndrome undergoing repair of CHD (including complete atrioventricular septal defect) compared with patients with normal karyotypes except among patients with single ventricle physiology . Several studies that included long‐term outcomes for complete atrioventricular septal defect repair have demonstrated a decreased rate of reoperation for left atrioventricular valve repair and for subaortic stenosis in patients with Down syndrome, which is likely related to valve and left ventricular outflow tract morphology differences …”
Section: Genetic Architecture Of Chdmentioning
confidence: 99%
“…Early surgical studies reported worse surgical outcomes in patients with Down syndrome undergoing repair for complete atrioventricular septal defect compared with patients without genetic syndromes . More recently, several studies have demonstrated equal or decreased risk of in‐hospital mortality for patients with Down syndrome undergoing repair of CHD (including complete atrioventricular septal defect) compared with patients with normal karyotypes except among patients with single ventricle physiology . Several studies that included long‐term outcomes for complete atrioventricular septal defect repair have demonstrated a decreased rate of reoperation for left atrioventricular valve repair and for subaortic stenosis in patients with Down syndrome, which is likely related to valve and left ventricular outflow tract morphology differences …”
Section: Genetic Architecture Of Chdmentioning
confidence: 99%
“…Os doentes com SD apresentam no pós-operatório frequentemente maior morbilidade dos que doentes com as mesmas lesões mas sem SD, 11,19 com maior taxa de complicações não cardíacas. De todas, as respiratórias estão descritas como sendo as mais frequentes, como o maior tempo de ventilação ou pneumotórax.…”
Section: Fatores De Risco Para Mortalidade Valor P Odds Ratiounclassified
“…De todas, as respiratórias estão descritas como sendo as mais frequentes, como o maior tempo de ventilação ou pneumotórax. 7,11,19 Este facto pode dever-se por um lado à maior taxa de obstrução crónica da via aérea, maior quantidade de secreções brônquicas e síndrome aspirativo crónico no contexto de refluxo gastroesofágico. 7 O nosso estudo corroborou esta maior prevalência de complicações respiratórias (25%), seguidas das complicações infeciosas (18%).…”
Section: Fatores De Risco Para Mortalidade Valor P Odds Ratiounclassified
See 1 more Smart Citation
“…Esta temática se encuentra fuera del objetivo de esta actualización, no obstante, el lector puede encontrar revisiones sobre esta materia 9,36,37 .…”
Section: Patología Cardíacaunclassified